Quality by Design: Concept to Applications - Swain, Suryakanta; Parhi, Rabinarayan; Jena, Bikash R.; Babu, Sitty Manohar (Current Drug Discovery Technologies, 2019)
Background: Quality by Design (QbD) is associated with a modern, systematic, scientific and novel approach which is concerned with pre-distinct objectives that not only focus on product, process understanding but also lead to process control. It predominantly signifies the design and product improvement and the manufacturing process in order to fulfill the predefined manufactured goods or final products quality characteristics. It is quite essential to identify the desired and required product performance report, such as Target Product Profile, typical Quality Target Product Profile (QTPP) and Critical Quality Attributes (CQA). Methods: This review highlighted the concepts of QbD design space, for critical material attributes (CMAs) as well as the critical process parameters that can totally affect the CQAs within which the process shall be unaffected thus, consistently manufacturing the required product. Risk assessment tools and design of experiments are its prime components. Results: This paper outlines the basic knowledge of QbD, the key elements; steps as well as various tools for QbD implementation in pharmaceutics field are presented briefly. In addition to this, quite a lot of applications of QbD in numerous pharmaceutical related unit operations are discussed and summarized. Conclusion: This article provides a complete data as well as the roadmap for universal implementation and application of QbD for pharmaceutical products.
Keywords: process analytical technology